Linking Antecedents, Processes, and Outcomes of Public Sector Innovation: A Complexity Theory Perspective - Alteneiji, Asma Omran Mohammed Alkhayyal; Tipu, Syed Awais Ahmad; Sarker, Abu Elias (International Review of Management and Marketing, 2024)
Drawing upon the complexity theory, the current study posits that public sector innovation (PSI) occurs in a complex adaptive system underpinning interactions’ effect between antecedents, processes, and outcomes of PSI. This rejects the notion of the traditional perspective of examining PSI through an Input-Process-Output framework. Four case studies of Federal Ministries in the United Arab Emirates are examined in which Government Excellence Model (GEM) was implemented. The findings revealed that the approaches adopted by selected ministries reflected self-organizing networks with feedback loops highlighting dynamic evolution. The national leadership vision, sense of competitiveness, and co-creation with the community played a significant role in implementing PSI. The current study focuses on the UAE's locally developed GEM, a model that introduces a novel philosophy centered on government entities' outcomes. It aligns these outcomes with government performance, citizen satisfaction and happiness, and competitive rankings. It intends to demonstrate how GEM sustains and shapes results across economic, social, and environmental dimensions.